2009
DOI: 10.1021/jm900576g
|View full text |Cite
|
Sign up to set email alerts
|

High Lipophilicity of meta Mn(III) N-Alkylpyridylporphyrin-Based Superoxide Dismutase Mimics Compensates for Their Lower Antioxidant Potency and Makes Them as Effective as Ortho Analogues in Protecting Superoxide Dismutase-Deficient Escherichia coli

Abstract: Lipophilicity/bioavailibility of Mn(III)N-alkylpyridylporphyrin-based SOD mimics has major impact on their in vivo ability to suppress oxidative stress. Meta isomers are less potent SOD mimics than ortho analogues, but are 10-fold more lipophilic and more planar. Enhanced lipophilicity contributes to their higher accumulation in cytosol of SOD-deficient E. coli, compensating for their lower potency; consequently both isomers exert similar-to-identical protection of SOD-deficient E. coli. Thus meta isomers may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 32 publications
5
75
0
Order By: Relevance
“…Assessment of partitioning between n-octanol and water revealed that each additional carbon atom added to the N-alkyl chains increases lipophilicity by 10-fold. An additional 10-fold increase of lipophilicity can be achieved by moving the N-alkyl groups from the ortho to meta N-pyridyl position (29). Here we demonstrate that a 50-fold increase in the lipophilicity of Zn N-alkylpyridylporphyrins produced by lengthening the side chains from 1 (methyl) to 6 carbons (hexyl), caused ϳ5-fold increase in the uptake of the PS by the cancer cells.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Assessment of partitioning between n-octanol and water revealed that each additional carbon atom added to the N-alkyl chains increases lipophilicity by 10-fold. An additional 10-fold increase of lipophilicity can be achieved by moving the N-alkyl groups from the ortho to meta N-pyridyl position (29). Here we demonstrate that a 50-fold increase in the lipophilicity of Zn N-alkylpyridylporphyrins produced by lengthening the side chains from 1 (methyl) to 6 carbons (hexyl), caused ϳ5-fold increase in the uptake of the PS by the cancer cells.…”
Section: Discussionmentioning
confidence: 63%
“…Uptake and subcellular localization of PSs in turn are controlled mainly by the net charge and lipophilicity of the molecule (22). Studies on photo-insensitive MnP analogs have shown that desired lipophilicity can be achieved by adding suitable alkyl substituents at the meso pyridyl positions, without affecting the net positive charge of the molecule (23,29). Assessment of partitioning between n-octanol and water revealed that each additional carbon atom added to the N-alkyl chains increases lipophilicity by 10-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Higher lipophilicity of meta Mn(III) N-alkylpyridylporphyrins drives their higher accumulation inside E. coli and compensates for lower antioxidant potency when compared with ortho analogues. Consequently, meta and ortho isomers are similarly efficacious in protecting SOD-deficient E. coli that lacks cytosolic SOD (178). Here, the most obvious case with ortho and meta N-ethylpyridylporpyrin is illustrated: meta isomer is~10-fold less SOD-active than the ortho species, but is 10-fold more lipophilic and accumulates~10-fold more in E. coli.…”
Section: K Other Modes Of Actionmentioning
confidence: 93%
“…Although the first evidence of their in vivo effects was published in J Biol Chem 1998 (29), meta isomers have been overlooked for decade. They are 3.6-to 15-fold less-potent SOD mimics, but are 10-fold more lipophilic and accumulate more in E. coli than ortho analogues (Table 1) (178). Figure 7 depicts the most obvious case; meta MnTE-3-PyP 5þ is an *10-fold less potent SOD mimic but is *10-fold more lipophilic than MnTE-2-PyP 5þ .…”
Section: E Bioavailability Of Mn Porphyrinsmentioning
confidence: 99%
“…Uptake of cationic metalloporphyrins by E. coli and mitochondria of eukaryotic cells is driven by the electrochemical proton gradient across membranes and is facilitated by the amphiphilic properties of the molecule. Depending on the alkyl chain length, MnPs accumulate more in membranes or in cytosol; the longer alkyl-chain analogs tend to accumulate more in membranes than in cytosol (66).…”
Section: The Accumulation Of Mnps By E Coli and S Cerevisiaementioning
confidence: 99%